The 2011 Institute of Cistercian Studies Conference - Cummings, Charles (Cistercian studies quarterly, 2011)
Information about several topics discussed at the 2011 Institute of Cistercian Studies Conference held at the Western Michigan University within the 46th annual International Congress on Medieval Studies on May 12 to 15, 2011 is presented. Topics of the conference are outlined which include monastic humanism, Cistercian spirituality and hagiography. The organizers of the event are highlighted which include E. Rozanne Elder and Karen McDougall.